Enzyme-assisted peeling of cold water shrimps (Pandalus borealis). (June 2018) - Dang, Tem Thi; Gringer, Nina; Jessen, Flemming; Olsen, Karsten; Bøknæs, Niels; Nielsen, Pia Louise; Orlien, Vibeke
Abstract: An enzymatic method to facilitate the peeling of cold water shrimps ( Pandalus borealis ) was developed. The protease solutions were used to mature the shrimps to promote shell-loosening prior to peeling. The efficiency of peeling enzyme-treated shrimps was evaluated by a new quantitative measurement based on the tensile force, presented as a peelability profile. It was found that enzymatic maturation efficiently improved the peelability of shrimps. The factors affecting the peelability of the enzyme-matured shrimps were the type of enzyme, enzyme concentration and maturation duration, while changes in pH had no impact. Maturation of shrimps in solutions of the endoproteases Endocut-01L (180 NU/g) and Endocut-03L (60 U/g) and the exoprotease Exocut-A0 (100 U/g) resulted in better peelability compared to shrimps matured in endoprotease Tail21 (65 U/mL) and 2% NaCl. A combination of 0.25% Endocut-03L and 0.25% Exocut-A0 for 20 h resulted in the best peeling of shrimps (100% completely peeled shrimps, 3 mJ/g work and 89% meat yield). Reuse of the enzyme solution was possible due to a 95% retention rate of proteolytic activity after two 20-h cycles of maturation. The studied enzymatic maturation offered a better shrimp product with respect to texture and color in comparison with an industrial brine-matured reference, i.e., 22% higher redness and 31% higher hardness. Industrial relevance: Enzymatic maturation is an attempt made as a pre-treatment to facilitate the removal of the shell from meat of shrimp. This approach would benefit the shrimp processing industry by 1) enhancing peeling efficiency that includes least efforts to remove the shell, high rate of completely peeled shrimps and high meat yield; 2) shortening the duration of maturation but still sufficiently loosening the shell for machine peeling; 3) performing as a chemical-free peeling aid, which may increase the preference of consumers over chemical compounds; and 4) being environmentally friendly since disposal of enzyme waste is harmless to the environment. Highlights: Commercial proteases were used to loosen shell from meat of shrimp prior to peeling. Peeling efficiency of shrimps was quantitatively evaluated. The enzymes ranging 0.25–2% v/v substantially improved the peelability of shrimp by reducing up to 70% peeling work. Reuse of enzyme solution was possible due to high retention rate of proteolytic activity i.e., 95% after two cycles of maturation. Enzyme-matured shrimps had better texture and color than an industrial reference.